2013
DOI: 10.1039/c2nr32981f
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional etching of silicon for the fabrication of low-dimensional and suspended devices

Abstract: In order to expand the use of nanoscaled silicon structures we present a new etching method that allows us to shape silicon with sub-10 nm precision. This top-down, CMOS compatible etching scheme allows us to fabricate silicon devices with quantum behavior without relying on difficult lateral lithography. We utilize this novel etching process to create quantum dots, quantum wires, vertical transistors and ultra-high-aspect ratio structures. We believe that this etching technique will have broad and significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Silicon is chosen as the mold material for its wide availability and varieties of relevant fabrication processes. In particular, recent developments in silicon dry etching produce smooth sidewall profiles [47][48][49] where the outside layer of the rough Si on the mold is converted to SiO2 during the thermal oxidation and subsequently removed by the BHF. After this treatment, the Si mold sidewall roughness is significantly reduced [50].…”
Section: Fabricationmentioning
confidence: 99%
“…Silicon is chosen as the mold material for its wide availability and varieties of relevant fabrication processes. In particular, recent developments in silicon dry etching produce smooth sidewall profiles [47][48][49] where the outside layer of the rough Si on the mold is converted to SiO2 during the thermal oxidation and subsequently removed by the BHF. After this treatment, the Si mold sidewall roughness is significantly reduced [50].…”
Section: Fabricationmentioning
confidence: 99%
“…Three dimensional (3D) silicon micro-and nanomachining has attracted a lot of interest in recent years for both research and industrial uses, and several promising applications have been proposed and demonstrated, e.g. vertically stacked silicon nanowires for field effect transistors (FET) [1], unified memory [2] and biosensors [3], shape-modified silicon nanopillars for quantum transport study [4] and FET [5], 3D silicon single cubic structures for 3D photonic crystal structures [6], etc. However, to easily fabricate 3D micro-and nanostructures, and simultaneously obtain a good size and shape control of the fabricated structures, is still considered to be difficult.…”
Section: Introductionmentioning
confidence: 99%
“…These nanopillars were fully converted into SiO 2 prior to their embedment in metal and into a suspended membrane. Upon modification of the applied (deep) reactive ion etch settings, the silicon nanopillars can have vertical or sculptured sidewalls [12][13][14], where the latter allows for the formation of quantum dots [13]. While in previous work Si pillars were converted into glass, in our contribution non-sculptured silicon nanopillars in combination conformal deposition steps, corner lithography [15][16] and sacrificial etch steps are applied to realize SiRNbased membranes containing massive arrays of parallel, hollow nanopores with embedded nano-cages.…”
Section: Introductionmentioning
confidence: 99%